A new species of Silene (Caryophyllaceae) from Türkiye - Altinözlü Haşi̇m; Aytaç Zeki̇; Çelemli̇ Ömür Gençay; Ertuğrul, Tuğba (Phytotaxa, 2025)
Silene aladagense (Caryophyllaceae) was described and illustrated as a new species from Aladağlar (Niğde Province, Türkiye). The species belongs to the sect. Caespitosae and it is similar to S. pharnaceifolia from which differs by the retrorsely puberulous stem and calyx and the lenght of anthophore. A detailed description, images, phenology, palynology, the IUCN assessment, and a identification key of the Turkish species of sect. Caespitosae are presented. In addition, the geographical distribution of the new species and other related species were mapped.